2015
DOI: 10.1007/s12550-015-0223-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the human urinary mycotoxin excretion patterns in Bangladesh, Germany, and Haiti using a rapid and sensitive LC-MS/MS approach

Abstract: An improved "dilute and shoot" LC-MS/MS multibiomarker approach was used to monitor urinary excretion of 23 mycotoxins and their metabolites in human populations from Asia (Bangladesh), Europe (Germany), and the Caribbean region (Haiti). Deoxynivalenol (DON), deoxynivalenol-3-glucuronide (DON-3-GlcA), T-2-toxin (T-2), HT-2-toxin (HT-2), HT-2-toxin-4-glucuronide (HT-2-4-GlcA), fumonisin B1 (FB1), aflatoxins (AFB1, AFB2, AFG1, AFG2, AFM1), zearalenone (ZEA), zearalanone (ZAN), their urinary metabolites α-zearala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
99
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 41 publications
13
99
2
2
Order By: Relevance
“…In total 19 studies were selected for ZEN, and its metabolites. The glucuronide forms ZEN14 ZEN14Oglucuronide was analysed by four authors (Abia et al, 2013;Ezekiel et al, 2014;Gerding et al, 2015;Cirlini et al, 2017). There is only one study in the dataset who analysed ZEN together with its phase I and glucuronides forms (Mauro et al, 2015).…”
Section: Zearalenonementioning
confidence: 99%
“…In total 19 studies were selected for ZEN, and its metabolites. The glucuronide forms ZEN14 ZEN14Oglucuronide was analysed by four authors (Abia et al, 2013;Ezekiel et al, 2014;Gerding et al, 2015;Cirlini et al, 2017). There is only one study in the dataset who analysed ZEN together with its phase I and glucuronides forms (Mauro et al, 2015).…”
Section: Zearalenonementioning
confidence: 99%
“…Resultate solcher Messungen belegen, dass die AFB1-Exposition in einigen Regionen Asiens und Afrikas bedenklich, in westlichen Industrielän-dern aber verhältnismäßig gering ist [14]. In keiner der Urinproben von erwachsenen Probanden in Deutschland konnte AFM1 detektiert werden [15]. Als Biomarker einer mittelfristigen Exposition kommen spezifische Addukte in DNA-Proben bzw.…”
Section: Aflatoxin Bunclassified
“…Human biomonitoring is considered a quite new frontier for establishing the real human exposure to mycotoxins. Recent results on this domain (Gerding et al, 2014(Gerding et al, , 2015Heyndrickx et al, 2015;Warth et al, 2012a,b) surprisingly revealed a level of exposure to mycotoxins above the widely accepted tolerable daily intake values, especially to DON, highlighting the importance to perform mycotoxin biomonitoring studies. Typical biomarkers of exposure are the parent toxins themselves, protein or DNA adducts, and/or major phase I or phase II metabolites (e.g.…”
Section: Main Challenges In Exposure Assessment To Multiple Mycotoxinsmentioning
confidence: 99%
“…The use of β-glucuronidase-assisted hydrolysis (in order to increase the levels of the parent toxins) (Ahn et al, 2010;Shephard et al, 2013;Solfrizzo et al, 2011Solfrizzo et al, , 2014Wallin et al, 2015), immunoaffinity columns (IAC) (Ahn et al, 2010;Rubert et al, 2011;Shephard et al, 2013;Solfrizzo et al, 2011Solfrizzo et al, , 2014Wallin et al, 2015) and solid-phase extraction (SPE) (Heyndrickx et al, 2015;Njumbe Ediage et al, 2012;Rodríguez-Carrasco et al, 2014a,b;Shephard et al, 2013;Solfrizzo et al, 2011Solfrizzo et al, , 2014Wallin et al, 2015) were applied by some authors as sample preparation and clean-up procedures. However, some studies have also successfully used the so-called dilute and shoot approach by omitting any cleanup procedure (Abia et al, 2013;Ezekiel et al, 2014;Gerding et al, 2014Gerding et al, , 2015Heyndrickx et al, 2015;Shephard et al, 2013;Warth et al, 2012a,b). Although the analysis of mycotoxins in human urine is another important data source for exposure assessment, some challenges are posed to human mycotoxin multibiomarker approaches.…”
Section: Main Challenges In Exposure Assessment To Multiple Mycotoxinsmentioning
confidence: 99%
See 1 more Smart Citation